Benchmarking of replication material for surface topography - Chew, Jia Rong (2016)
Surface finish measurements are crucial in various industries and applications, including but not limited to engineering applications, aerospace, marine and automotive industries, to understand and test for the functionality or performance of a component. This is due to the ability of surface topography to capture information about machining or manufacturing processes, and also the wear and tear quality of the part, which can be used to indicate any deterioration or drop in performance of the part. However, sometimes, direct surface measurement may be difficult to perform without damaging the part such as when the component is inaccessible or too large to be moved, in which alternative non-destructive measurement methods would need to be used instead. A common way is surface replication, in which the inverse of the original sample is replicated and taken to measurement instead. In that case, it is also even more important to understand the fidelity and performance of the replicating material in replicating the original surface topography, such that an adequate material can be chosen for use. Polymerising agents were tested on in this study, to reach an appropriate benchmarking or classification of use of different materials for different surface roughness. The materials ranged from dental impression materials, as well as industrial grade Repliset and Microset. Hence in order to determine the accuracy of the surface replication, a standardized set of roughnesses from a measured, calibrated sample was used, which includes surface roughnesses of 0.1 µm, 0.2 µm, 0.4 µm, 0.8 µm, 1.6 µm, 3.2 µm, 6.3 µm and 12.5 µm. Replicating materials which included a range of viscosities were then used to replicate the designated surfaces, and then measured on an optical non-contact measuring instrument for 2D and 3D analysis. Further analysis is done to observe trends between fidelity and surface roughness, fidelity and material viscosities at different 2D and 3D surface parameters that are specially chosen as a characteristic of surface topography. From there, materials with low accuracies will be able to be singled out as well as surface roughness up to a certain level may not be adequate for replication by most materials. This can help generate an appropriate benchmarking according to the results that can aid replication usage in the future. However, 3D results and analysis, though more representative of the surface examined, also was limited due to several possible source of errors such as inconsistencies in the exact location measured on the samples and also limited materials being measured on 3D. This then, helps to propose further analysis and areas for improvement, and also findings that can help act as a basis for further research and characterization.